Psychological and behavioral examinations in cyber security - McAlaney, John 1979; Frumkin, Lara Anne 1972; Benson, Vladlena 1976 (Advances in Digital Crime, forensics, and Cyber Terrorism Book Series, 2018)
"This book addresses the emerging importance of digital psychology and the opportunities offered by cyber researchers. It provides the resources necessary for academics, policy makers, technology developers and managers to improve cybersecurity and manage individual decision making more effectively"